Composite current collector, preparation method thereof and battery

By ion cleaning of the polypropylene substrate layer, forming a regular pore structure, and filling the conductive layer, the problem of poor adhesion of the metal layer in the composite liquid collecting is solved, its stability and electrical properties are improved, and it is suitable for use in lithium batteries. application.

CN119230835APending Publication Date: 2024-12-31SUZHOU ZHENLI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411526333.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The adhesion of the metal layer in the composite fluid collecting fluid on the polypropylene substrate layer is poor, resulting in poor stability of the composite fluid collecting fluid, affecting its mass production and industrialization progress.

Method used

By ionically cleaning the polypropylene substrate layer to form hanging bonds and forming a regularly distributed pore structure on its surface, the conductive layer is filled to improve the bond strength between the metal layer and the polypropylene substrate layer.

Benefits of technology

The structural stability and electrical properties of the composite fluid collector are significantly improved, and the service life and cycle stability of the battery are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230835A_ABST
    Figure CN119230835A_ABST
Patent Text Reader

Abstract

The invention discloses a composite current collector, a preparation method thereof and a battery, and belongs to the technical field of secondary batteries. The preparation method of the composite current collector comprises the following steps: S1, carrying out ion cleaning on at least one side of the polypropylene base material layer to form dangling bonds on the surface of the polypropylene base material layer; a first inorganic layer is formed on the surface of the polypropylene base material layer, a plurality of pore structures penetrating through the first inorganic layer are arranged on the first inorganic layer, and the pore structures extend into the polypropylene base material layer and do not penetrate through the polypropylene base material layer; the pore structures are regularly distributed in the first inorganic layer; s2, filling a conductive layer in the hole structure, wherein the conductive layer is located on the first inorganic layer; the conductive layer comprises a second inorganic layer and a metal layer, the hole structure is filled with the second inorganic layer, the second inorganic layer is located on the first inorganic layer, and the metal layer is located on the second inorganic layer. The composite current collector prepared by the method can improve the structural stability of the composite current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite current collector, a preparation method thereof, and a battery. Background Art

[0002] With the development of emerging industries such as new energy vehicles and energy storage, the output of lithium batteries has shown explosive growth. Battery factories and vehicle manufacturers have put forward more stringent requirements on the high energy density, high safety, quality improvement and efficiency enhancement of lithium battery materials.

[0003] The current collector is a structure or part that collects current inside a lithium battery. Its function is to carry the positive and negative active materials and collect the battery active materials to generate a large output current. Compared with traditional current collectors, composite current collectors adopt a "metal-polymer material-metal" "sandwich" structure, which has the advantages of high safety, long life, high energy density, and low cost. It is expected to become the mainstream application of lithium battery positive and negative current collectors in the future.

[0004] The main polymer layer materials in composite current collectors are polypropylene (PP) and polyethylene terephthalate (PET). PET is less resistant to electrolyte corrosion than PP due to the ester functional groups in its molecular structure, so PP is more suitable as a substrate in composite current collectors. However, metal materials have poor adhesion on PP and the stability of composite current collectors is poor, which makes the mass production of composite current collectors more difficult and delays its industrialization progress. Therefore, how to provide a composite current collector with high structural stability is an urgent problem to be solved in the field of secondary batteries. Summary of the invention

[0005] Based on the above-mentioned deficiencies, the present application provides a composite current collector, a preparation method thereof and a battery to improve the problem of poor structural stability of the composite current collector in the related art.

[0006] This application is implemented as follows:

[0007] In a first aspect, an example of the present application provides a method for preparing a composite current collector, comprising:

[0008] S1. Performing ion cleaning on at least one side of the polypropylene substrate layer to form dangling bonds on the surface of the polypropylene substrate layer; forming a first inorganic layer on the surface of the polypropylene substrate layer, and providing a plurality of pore structures penetrating the first inorganic layer on the first inorganic layer, wherein the pore structures extend into the polypropylene substrate layer and do not penetrate the polypropylene substrate layer; and the pore structures are regularly distributed in the first inorganic layer;

[0009] S2. Filling a conductive layer in the hole structure, and the conductive layer is located on the first inorganic layer; the conductive layer includes a second inorganic layer and a metal layer, the second inorganic layer is filled in the hole structure and is located on the first inorganic layer, and the metal layer is located on the second inorganic layer.

[0010] In the above implementation process, when preparing the composite current collector, a first inorganic layer is formed on at least one side of the polypropylene substrate layer, and a plurality of pore structures are arranged at the first inorganic layer, which penetrate the first inorganic layer and extend to the polypropylene substrate layer but do not penetrate the polypropylene substrate layer. Then, a conductive layer is arranged on the first inorganic layer, and the conductive layer is filled in the pore structure, so that the second inorganic layer in the conductive layer can be connected to the first inorganic layer in a face-to-face contact form, and can be connected to the first inorganic layer in an interlocking manner, and the second inorganic layer in the conductive layer can also be connected to the polypropylene substrate layer in a face-to-face contact form, and can also be connected to the polypropylene substrate layer in an interlocking manner. The pore structure is regularly distributed, which can make the bonding between the polypropylene substrate layer and the conductive layer more firm while ensuring the structural strength of the polypropylene substrate layer, thereby improving the structural stability of the composite current collector.

[0011] Ion cleaning of the surface of the polypropylene substrate layer can, on the one hand, form dangling bonds such as CO bonds on the surface of the polypropylene substrate layer, enable the polypropylene substrate layer to form a bond with the first inorganic layer, and improve the structural stability of the composite current collector; on the other hand, it can also form a rough surface on the surface of the polypropylene substrate layer, and the combination of the rough surface and the first inorganic layer can further improve the structural stability of the composite current collector.

[0012] In combination with the first aspect, in an optional embodiment of the present application, the polypropylene substrate layer is ion cleaned to form dangling bonds on the surface of the polypropylene substrate layer, including:

[0013] The polypropylene substrate layer is ion cleaned, the power of the ion cleaning is 0.01-5kW, the speed of the ion cleaning is 0.1-20m / min, the process gas for ion cleaning is selected from at least one of oxygen, nitrogen, argon, hydrogen, and methane, and the gas volume of the process gas is 10-500sccm.

[0014] In the above implementation process, the polypropylene substrate layer is ion-cleaned, the power of ion cleaning is 0.01-5KW, the speed of ion cleaning is 0.1-20m / min, the process gas of ion cleaning is selected from at least one of oxygen, nitrogen, argon, hydrogen, and methane, and the gas volume of the process gas is 10-500sccm, which can not only remove impurities on the surface of the polypropylene substrate layer, but also roughen the surface of the polypropylene substrate layer to form a rough surface, and can also activate the surface of the polypropylene substrate layer to form dangling bonds, which can form bonds with the first inorganic layer to improve the bonding strength between the first inorganic layer and the polypropylene substrate layer. Ion cleaning the polypropylene substrate layer within a specific power range can also reduce the impact of ion cleaning on the mechanical properties of the polypropylene substrate layer.

[0015] In combination with the first aspect, in an optional embodiment of the present application, the pore structure penetrates the opposite ends of the first inorganic layer in the width direction, and the multiple pore structures are evenly spaced; or, the multiple pore structures are arranged in an array in the first inorganic layer.

[0016] The composite current collector is usually in the form of a sheet with a certain width and length. In the above implementation process, the pore structure penetrates the opposite ends of the width direction of the first inorganic layer, and multiple pore structures are arranged at intervals, which can form multiple binding positions for the conductive layer in the length direction of the polypropylene substrate layer. The length of each pore structure is relatively short, which can further reduce the probability of separation between the conductive layer and the polypropylene substrate layer, and improve the structural stability of the composite current collector.

[0017] Multiple hole structures are arranged in an array on the first inorganic layer, which can make the conductive layer and the polypropylene substrate layer regularly combined. When encountering external force, the force at each bonding position between the conductive layer and the polypropylene substrate layer is relatively uniform, which can further improve the bonding force between the conductive layer and the metal layer and improve the structural stability of the composite current collector.

[0018] In combination with the first aspect, in an optional embodiment of the present application, in step S1, a plurality of pore structures penetrating the first inorganic layer are provided on the first inorganic layer, and the pore structures extend into the polypropylene substrate layer and do not penetrate the polypropylene substrate layer, including:

[0019] The first inorganic layer is laser etched to form a plurality of first through hole structures spaced apart to expose the polypropylene substrate layer; the polypropylene substrate layer is etched at positions corresponding to the first through hole structures using an etching solution to form second blind hole structures, and the first through hole structures and the second blind hole structures together form a hole structure.

[0020] In the above implementation process, the first inorganic layer is etched by laser etching technology, and a through-hole structure with a specific shape, size and spacing distance and arranged regularly such as an array can be formed at the first inorganic layer as needed. The first inorganic layer after laser etching is used as a mask for the polypropylene substrate layer. When the polypropylene substrate layer is etched by etching liquid, the etching liquid can directionally etch the position of the polypropylene substrate layer corresponding to the through-hole structure to form a second blind hole structure with a similar arrangement mode, shape and size to the through-hole structure. The first through-hole structure is connected to the second blind hole structure to form a hole structure together. Using laser etching technology, a micro-nano-sized hole structure can be formed.

[0021] In combination with the first aspect, in an optional embodiment of the present application, the ratio of the depth of the second blind hole structure to the thickness of the polypropylene substrate layer is 1:4.5-10.

[0022] Optionally, the depth of the second blind hole structure is 1-1000 nm.

[0023] In the above implementation process, the ratio of the depth of the second blind hole structure to the thickness of the polypropylene substrate layer is 1:4.5-10, which can reduce the influence of the second blind hole structure on the structural strength of the polypropylene substrate layer.

[0024] In combination with the first aspect, in an optional embodiment of the present application, along the first direction, the ratio of the width of the hole structure to the spacing between two adjacent hole structures is 1:1-20.

[0025] Optionally, the width of the pore structure is 1-500 nm, and the distance between two adjacent pore structures is 1-500 nm.

[0026] In the above implementation process, along the first direction, the ratio of the width of the hole structure to the spacing between two adjacent hole structures is 1:1-20, which can reduce the influence of the hole structure on the structural strength of the polypropylene substrate layer, and facilitate the conductive layer to be filled in the hole structure and stably combined with the polypropylene substrate layer, which can further improve the structural stability of the composite current collector.

[0027] In combination with the first aspect, in an optional embodiment of the present application, the depth of the second blind hole structure is 50-100 nm; and / or the width of the hole structure is 150-200 nm, and the spacing between two adjacent hole structures is 150-200 nm.

[0028] In combination with the first aspect, in an optional embodiment of the present application, etching the polypropylene substrate layer at a position corresponding to the first through-hole structure using an etching solution to form a second blind hole structure includes:

[0029] An acid solution is applied to the side of the first inorganic layer facing away from the polypropylene substrate layer, so that the acid solution passes through the first through-hole structure to etch the polypropylene substrate layer to form a second blind hole structure.

[0030] In the above implementation process, the polypropylene substrate layer has good chemical stability, high temperature cycle resistance and light weight, and when the composite current collector is applied to a secondary battery, it can improve the electrical properties of the secondary battery such as cycle stability and battery capacity. An acid solution is applied to the side of the first inorganic layer away from the polypropylene substrate layer, and the acid solution can pass through the first through-hole structure at the first inorganic layer and contact the polypropylene substrate layer, and the polypropylene substrate layer at the contact position is etched to form a second blind hole structure.

[0031] In combination with the first aspect, in an optional embodiment of the present application, the materials of the first inorganic layer and the second inorganic layer are independently selected from at least one of metals, alloys or oxides of copper, aluminum, chromium or nickel; the material of the metal layer is selected from at least one of copper, aluminum, chromium or nickel.

[0032] Optionally, the mass fraction of the etching liquid is an acid solution of 10%-50%, the application temperature is 0-50° C., and the etching time is 1-60 s.

[0033] Optionally, the acid solution is selected from one or more of sulfuric acid, nitric acid, hydrobromic acid, chromic acid, selenic acid, perchloric acid, acetic acid, propionic acid, fatty acid, oleic acid, oxalic acid, maleic acid, hydroxypropionic acid, monochloroacetic acid or peracetic acid.

[0034] In the above implementation process, the material of the first inorganic layer and the second inorganic layer is the same as that of the metal layer, or is an alloy or oxide thereof, which can improve the bonding strength between the first inorganic layer and the second inorganic layer and between the second inorganic layer and the metal layer, and further improve the structural stability of the composite current collector.

[0035] The polypropylene substrate layer is etched at a temperature of 0-50°C using an acid solution with a mass fraction of 10%-50% for an etching time of 1-60s, which can reduce the impact of the acid solution on the first inorganic layer and the first through-hole structure, so as to form a second blind hole structure with a specific arrangement and shape size on the polypropylene substrate layer.

[0036] In combination with the first aspect, in an optional embodiment of the present application, the preparation method further includes a cleaning step before step S1, and the cleaning step includes:

[0037] S01. Ultrasonic cleaning of the polypropylene substrate layer is performed using distilled water, anhydrous ethanol, acetone, and anhydrous ethanol in sequence, followed by vacuum baking.

[0038] In the above implementation process, before the first inorganic layer is formed on the surface of the polypropylene substrate layer, the polypropylene substrate layer is ultrasonically cleaned with distilled water, anhydrous ethanol, acetone, and anhydrous ethanol in sequence, and then vacuum-baked, which can remove the chemical reagents and dirt remaining on the surface of the polypropylene substrate layer and improve the bonding strength between the first inorganic layer and the polypropylene substrate layer.

[0039] In combination with the first aspect, in an optional embodiment of the present application, in step S1, a first inorganic layer is formed on two opposite surfaces of the polypropylene substrate layer.

[0040] In the above implementation process, a first inorganic layer and a corresponding pore structure are formed on both sides of the polypropylene substrate layer, and subsequently a conductive layer can be formed at the first inorganic layer and the pore structure on each side, so that the surface layers on both sides of the composite current collector are metal layers, which can improve the electrical properties of the composite current collector.

[0041] In combination with the first aspect, in an optional embodiment of the present application, in step S2, filling the hole structure with a conductive layer, and the conductive layer is located on the first inorganic layer, includes:

[0042] A second inorganic layer is formed on a side of the first inorganic layer away from the polypropylene substrate layer, and at least a portion of the second inorganic layer is filled in the hole structure; and a metal layer is formed on a side of the second inorganic layer away from the first inorganic layer.

[0043] In the above implementation process, a second inorganic layer is formed on the side of the first inorganic layer away from the polypropylene substrate layer, and at least a portion of the second inorganic layer is filled in the hole structure. The second inorganic layer can be used to connect the polypropylene substrate layer, the first inorganic layer and the metal layer, thereby enhancing the bonding force between the layer structures and improving the structural stability of the composite current collector.

[0044] In combination with the first aspect, in an optional embodiment of the present application, the preparation method also includes: before forming a metal layer on the side of the second inorganic layer facing away from the first inorganic layer, ion etching is performed on the side of the second inorganic layer facing away from the first inorganic layer, and the parameters of the ion etching include: bias voltage of -600 to -700 V, current of 0.4-0.5 A, temperature of 40-50°C, etching time of 15-20 min, and the etching process gas is selected from at least one of oxygen, nitrogen, argon, hydrogen or methane.

[0045] In the above implementation process, ion etching is performed on the second inorganic layer, so that a velvet surface can be formed on the surface of the second inorganic layer, thereby improving the bonding strength between the second inorganic layer and the metal layer.

[0046] In combination with the first aspect, in an optional embodiment of the present application, the preparation methods of the first inorganic layer, the second inorganic layer and the metal layer are independently selected from at least one of magnetron sputtering deposition, chemical vapor deposition, pulsed laser deposition or ion plating.

[0047] Optionally, the thickness of the first inorganic layer and the second inorganic layer is 1-100 nm;

[0048] Optionally, the thickness of the metal layer is 50-200 nm.

[0049] In the above implementation process, the first inorganic layer, the second inorganic layer and the metal layer are prepared by magnetron sputtering deposition, chemical vapor deposition, pulsed laser deposition or ion plating, which can improve the bonding strength within the layer structure and between the layers. The thickness of the first inorganic layer and the second inorganic layer is 1-100nm, and the thickness of the metal layer is 50-200nm, which can not only avoid the bonding strength between the layers due to the thickness of the layer structure being too thin or too thick, but also reduce the internal resistance of the composite current collector and improve the electrical properties of the composite current collector.

[0050] In a second aspect, the present application provides a composite current collector prepared according to the preparation method provided in the first aspect.

[0051] In the above implementation process, the composite current collector prepared according to the preparation method provided in the first aspect has good structural stability.

[0052] In a third aspect, the present application example provides a battery, comprising the composite current collector provided in the second aspect.

[0053] In the above implementation process, the composite current collector provided in the second aspect of the present application is applied to the battery, and the composite current collector can improve the energy density and safety of the battery. In addition, the composite current collector provided in the second aspect of the present application has good structural stability, and the metal layer located on the surface is not easy to fall off, which can improve the service life and electrical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0055] Figure 1 Schematic diagram of the structure of the composite current collector provided for comparison technology;

[0056] Figure 2 A schematic diagram of the preparation process of the composite current collector provided in the embodiment of the present application;

[0057] Figure 3 A first schematic diagram of the intermediate structure obtained in step S1;

[0058] Figure 4 A schematic diagram of the structure of the composite current collector prepared in step S2;

[0059] Figure 5 This is a schematic structural diagram of forming a first inorganic layer on one side of a polypropylene substrate layer in step S1;

[0060] Figure 6 This is a schematic structural diagram of forming a first inorganic layer on both sides of the polypropylene substrate layer in step S11;

[0061] Figure 7 A schematic structural diagram of step S12 in which the first inorganic layer is laser-etched to form a plurality of first through-hole structures arranged at intervals to expose the polypropylene substrate layer;

[0062] Figure 8 is a schematic diagram of a first distribution of a first through-hole structure;

[0063] Fig. 9 is a schematic diagram of a second distribution of the first through-hole structure;

[0064] Fig.10 A schematic diagram of the structure after forming the second inorganic layer in step S21;

[0065] Fig.11 XPS graph of the polypropylene substrate layer before ion cleaning provided in Test Example 1;

[0066] Fig.12XPS graph of the polypropylene substrate layer after ion cleaning provided in Test Example 1;

[0067] Fig.13 The peeling force test curve provided for Test Example 2;

[0068] Fig.14 Cyclic performance test provided for Test Example 3.

[0069] Icon: 100-composite current collector; 101-polypropylene substrate layer; 10-conductive layer; 102-metal layer; 103-first inorganic layer; 104-hole structure; 1041-first through hole structure; 1042-second blind hole structure; 105-second inorganic layer; L1-width; L2-spacing. DETAILED DESCRIPTION

[0070] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0071] The current collector is a structure or part that collects current inside a lithium battery. Its function is to carry the positive and negative active materials and collect the battery active materials to generate a larger output current.

[0072] With the development of new energy vehicles, energy storage and other emerging industries, battery factories and vehicle manufacturers have put forward more stringent requirements for high energy density, high safety, quality and efficiency improvement of lithium battery materials. Compared with traditional current collectors, composite current collector 100 has the advantages of high safety, long life, high energy density and low cost, and is expected to become the mainstream application of lithium battery positive and negative current collectors in the future.

[0073] See also Figure 1 Generally, the composite current collector 100 has a sandwich structure, including a metal layer 102-polypropylene substrate layer 101-metal layer 102. The substrate layer in the composite current collector 100 is a polymer material, which has a lower density than metal materials, and can reduce the weight of the current collector, thereby increasing the battery density. In addition, the polymer material can also inhibit the formation of dendrites and has a circuit-breaking effect, which can improve the safety of the battery.

[0074] At present, the polymer materials used in the substrate layer of the composite current collector 100 are mainly polypropylene (PP) and polyethylene terephthalate (PET). Compared with PP, PET is not resistant to electrolyte corrosion, which will affect the service life of the battery. The substrate layer in the composite current collector 100 is prepared with PP material. PP has good resistance to electrolyte corrosion and high temperature cyclability, which can improve the cyclability of the battery.

[0075] However, the metal layer 102 in the composite current collector 100 has poor adhesion on PP, the composite current collector 100 has low bonding strength and poor stability, which makes it difficult to mass produce the composite current collector 100 and delays its industrialization progress. Therefore, how to provide a composite current collector 100 with high structural stability is an urgent problem to be solved in the current secondary battery field.

[0076] In order to improve the bonding strength between the metal layer 102 and the polypropylene substrate layer 101, the inventors tried to roughen the surface of the polypropylene substrate layer 101 using acid, alkali or other etching methods or mechanical polishing methods, and then deposited the metal layer 102 on the roughened substrate surface.

[0077] However, the inventors found that the bonding strength between the metal layer 102 and the polypropylene substrate layer 101 and the mechanical properties of the composite current collector 100 formed by treating the polypropylene substrate layer 101 with the roughening method and then plating the metal layer 102 still need to be improved.

[0078] The inventors analyzed that after the surface of the polypropylene substrate layer 101 is roughened by acid, alkali or other etching methods or mechanical polishing, a velvet structure with various shapes, uneven sizes and irregular distribution is often formed on the surface of the polypropylene substrate layer 101. When the metal layer 102 is subsequently deposited, the metal material cannot be effectively filled in part of the velvet structure, which is not conducive to improving the bonding strength between the metal layer 102 and the polypropylene substrate layer 101. In addition, the traditional etching process is not easy to control, and the mechanical properties of the polypropylene substrate layer 101 are easily destroyed during the etching process, which is not conducive to further improving the structural stability of the composite current collector 100.

[0079] Based on this, the embodiment of the present application provides a method for preparing a composite current collector 100, thereby improving the structural stability of the composite current collector 100 to a certain extent. In order to make the purpose, technical solution and advantages of the embodiment of the present application clearer, the technical solution in the embodiment of the present application will be clearly and completely described below in conjunction with the drawings in the embodiment of the present application.

[0080] See also Figure 2 , the present application embodiment provides a method for preparing a composite current collector 100, comprising:

[0081] S1. Ion cleaning is performed on at least one side of the polypropylene substrate layer 101 to form dangling bonds on the surface of the polypropylene substrate layer 101; a first inorganic layer 103 is formed on the surface of the polypropylene substrate layer 101, and a plurality of pore structures 104 penetrating the first inorganic layer 103 are provided on the first inorganic layer 103, wherein the pore structures 104 extend into the polypropylene substrate layer 101 and do not penetrate the polypropylene substrate layer 101. The pore structures 104 are regularly distributed in the first inorganic layer 103.

[0082] S2. Fill the conductive layer 10 in the hole structure 104 and the conductive layer 10 is located on the first inorganic layer 103; the conductive layer 10 includes a second inorganic layer 105 and a metal layer 102, the second inorganic layer 105 is filled in the hole structure 104 and is located on the first inorganic layer 103, and the metal layer 102 is located on the second inorganic layer 105.

[0083] Among them, see Figure 3 , Figure 3 This is a first schematic diagram of the intermediate structure obtained in step S1. Figure 4 , Figure 4 Schematic diagram of the structure of the composite current collector 100 prepared in step S2.

[0084] A first inorganic layer 103 is disposed on at least one side of the polypropylene substrate layer 101, and a plurality of hole structures 104 are disposed on the first inorganic layer 103, which penetrate the first inorganic layer 103 and extend to the polypropylene substrate layer 101 but do not penetrate the polypropylene substrate layer 101. The conductive layer 10 can be disposed on the first inorganic layer 103 and filled in the hole structure 104. The conductive layer 10 and the polypropylene substrate layer 101 are indirectly connected by the first inorganic layer 103, and the conductive layer 10 filled in the hole structure 104 is directly connected to the polypropylene substrate layer 101 and the first inorganic layer 103. The bonding strength between the conductive layer 10 and the polypropylene substrate layer 101 can be improved, and the metal layer 102 on the surface of the conductive layer 10 is not easy to fall off, thereby improving the structural stability of the composite current collector 100.

[0085] The metal layer 102 in the conductive layer 10 is used for conducting electricity.

[0086] Further, the polypropylene substrate layer 101 may be selected from polypropylene substrate layers 101 having a thickness of 4.5 μm.

[0087] Furthermore, in some possible embodiments, the material of the first inorganic layer 103 may be selected from at least one of metals, alloys or oxides of copper, aluminum, chromium or nickel.

[0088] Exemplarily, the material of the first inorganic layer 103 can be selected from at least one of copper, aluminum, chromium, nickel, copper alloy, aluminum alloy, chromium alloy, nickel alloy, copper-aluminum alloy, chromium-nickel alloy, copper-aluminum-chromium-nickel alloy, copper oxide, aluminum oxide, chromium oxide or nickel oxide.

[0089] Exemplarily, the material of the first inorganic layer 103 may be selected from copper oxide.

[0090] The conductive layer 10 and the polypropylene substrate layer 101 are connected by a first inorganic layer 103 made of a metal, alloy or oxide such as copper, aluminum, chromium or nickel. The first inorganic layer 103 has a material that is the same as, similar to, or has the same or similar elements as the metal layer 102, and can serve as a transition layer to enhance the bonding strength between the conductive layer 10 and the polypropylene substrate layer 101.

[0091] In step S1, the present application does not limit how to form the first inorganic layer 103 on at least one side of the polypropylene substrate layer 101. In some possible embodiments, please continue to refer to Figure 2 , the preparation method comprises:

[0092] S11 , forming a first inorganic layer 103 on at least one side of the polypropylene substrate layer 101 by magnetron sputtering deposition, chemical vapor deposition, pulsed laser deposition or ion plating.

[0093] See also Figure 5 , Figure 5 It is a schematic structural diagram of forming a first inorganic layer 103 on at least one side of the polypropylene substrate layer 101 in step S1.

[0094] Furthermore, a first inorganic layer 103 with a thickness of 1-100 nm may be formed on at least one side of the polypropylene substrate layer 101 .

[0095] Illustratively, the thickness of the first inorganic layer 103 may be one of 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, or a range between any two thereof.

[0096] The thickness of the first inorganic layer 103 is 1-100 nm, which can improve the structural stability of the composite current collector 100. If the thickness of the first inorganic layer 103 is too low, it is not conducive to forming the pore structure 104 at the first inorganic layer 103, and it will affect the bonding strength between the polypropylene substrate layer 101 and the first inorganic layer 103. If the thickness of the first inorganic layer 103 is too thick, the bonding strength between the first inorganic layer and the polypropylene substrate layer 101 and between the subsequent conductive layer 10 and the first inorganic layer 103 will be reduced.

[0097] Furthermore, the thickness of the first inorganic layer 103 may be 5-10 nm.

[0098] For further information, see Figure 6 , the first inorganic layer 103 may be disposed on both sides of the polypropylene base layer 101 .

[0099] For example, the polypropylene substrate layer 101 can be placed in a vacuum magnetron sputtering coating device, and the chamber of the device is evacuated to a vacuum degree of less than 5×10 -3 Pa, and the temperature was adjusted to 25° C. Oxygen was introduced into the chamber to maintain the gas pressure at 0.18 Pa, and a vacuum magnetron sputtering coating method was used to deposit on the upper and lower sides of the polypropylene substrate layer 101 with a deposition current of 10 A for 3 minutes, and a first inorganic layer 103 with a thickness of 10 nm and made of copper oxide was formed on the upper and lower layers of the polypropylene substrate layer 101.

[0100] Further, in step S1, the present application does not limit how to set a plurality of hole structures 104 penetrating the first inorganic layer 103 on the first inorganic layer 103, and the hole structure 104 extends into the polypropylene substrate layer 101 and does not penetrate the polypropylene substrate layer 101. In a possible embodiment, please continue to refer to Figure 2 , the preparation method further comprises:

[0101] S12 , performing laser etching on the first inorganic layer 103 to form a plurality of first through-hole structures 1041 arranged at intervals to expose the polypropylene substrate layer 101 .

[0102] S13 , using an etching solution to etch the position of the polypropylene substrate layer 101 corresponding to the first through hole structure 1041 to form a second blind hole structure 1042 . The first through hole structure 1041 and the second blind hole structure 1042 together form a hole structure 104 .

[0103] Among them, see Figure 7 and Figure 3 , Figure 7 The schematic diagram of the structure of step S12 is that the first inorganic layer 103 is laser-etched to form a plurality of first through-hole structures 1041 arranged at intervals to expose the polypropylene substrate layer 101. The schematic diagram of step S13 is that the polypropylene substrate layer 101 is etched at the position corresponding to the first through-hole structure 1041 to form a second blind hole structure 1042. Figure 3 .

[0104] The first inorganic layer 103 is etched by laser etching technology, and a first through hole structure 1041 with a specific shape, size and spacing distance and arranged regularly in an array or the like can be formed at the first inorganic layer 103 as needed. The first inorganic layer 103 after laser etching is used as a mask for the polypropylene substrate layer 101, and the polypropylene substrate layer 101 is etched by an etching liquid. The etching liquid can directionally etch the position of the polypropylene substrate layer 101 corresponding to the first through hole structure 1041 to form a second blind hole structure 1042 with a similar arrangement mode, shape and size to the first through hole structure 1041. The first through hole structure 1041 is connected with the second blind hole structure 1042 to form a hole structure 104 together.

[0105] Further, the present application does not limit the specific shape, size and distribution of the first through-hole structure 1041. In some possible embodiments, please refer to Figure 8 and Fig. 9 , multiple first through-hole structures 1041 are regularly distributed.

[0106] In some possible embodiments, a plurality of first through-hole structures 1041 are distributed in an array.

[0107] Exemplarily, the first inorganic layer 103 is rectangular in width and length directions, and the plurality of first through-hole structures 1041 are distributed in a rectangular array along the width and length directions.

[0108] Exemplarily, the first inorganic layer 103 is circular, and the plurality of first through-hole structures 1041 are distributed in a ring array along the diameter direction.

[0109] Further, in a possible embodiment, please continue to refer to Fig. 9 The first inorganic layer 103 is a rectangle having a length direction and a width direction. The first through-hole structure 1041 penetrates two opposite ends of the first inorganic layer 103 in the width direction. A plurality of first through-hole structures 1041 are evenly spaced.

[0110] Alternatively, in a possible embodiment, please continue to refer to Figure 8 The transverse cross-section of the first through-hole structure 1041 may be circular, and a plurality of circular first through-hole structures 1041 are distributed in an array.

[0111] Alternatively, in a possible embodiment, the transverse cross-section of the first through-hole structure 1041 may be wavy, and a plurality of wavy first through-hole structures 1041 are distributed in an array.

[0112] The first through-hole structures 1041 are regularly distributed, and subsequently a regularly distributed second blind hole structure 1042 can be formed on the polypropylene substrate layer 101. The formation of a plurality of regularly distributed second blind hole structures 1042 on the polypropylene substrate layer 101 can, on the one hand, reduce the influence of the formation of the second blind hole structures 1042 on the mechanical properties of the polypropylene substrate layer 101, and on the other hand, can make the conductive layer 10 and the polypropylene substrate layer 101 have regular combination, improve the combination firmness between the conductive layer 10 and the metal layer 102, and improve the structural stability of the composite current collector 100.

[0113] Further, in some possible embodiments, along the first direction, the ratio of the width L1 of the first through hole structure 1041 to the interval L2 between two adjacent first through hole structures 1041 is 1:1-20.

[0114] Exemplarily, L1:L2 can be one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, or a range between any two of them.

[0115] The first direction may coincide with the array direction.

[0116] In some possible embodiments, the width L1 of the first through-hole structure 1041 may be 1-500 nm, and the distance L2 between two adjacent first through-hole structures 1041 may be 1-500 nm.

[0117] Exemplarily, the width L1 of the first through hole structure 1041 may be one of 1 nm, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, or a range between any two of them.

[0118] For example, the width L1 of the first through-hole structure 1041 may be 150 nm, and the interval L2 between two adjacent first through-hole structures 1041 may be 150 nm.

[0119] For example, the width L1 of the first through-hole structure 1041 may be 50 nm, and the interval L2 between two adjacent first through-hole structures 1041 may be 50 nm.

[0120] For example, the width L1 of the first through-hole structure 1041 may be 10 nm, and the distance L2 between two adjacent first through-hole structures 1041 may be 200 nm.

[0121] The ratio of the width L1 of the first through-hole structure 1041 to the spacing L2 between two adjacent first through-hole structures 1041 is 1:1-20, which can facilitate the conductive layer 10 to be filled in the hole structure 104 and stably combined with the polypropylene substrate layer 101, further improving the structural stability of the composite current collector 100. If the ratio of the width L1 of the first through-hole structure 1041 to the spacing L2 is too small or too large, the bonding strength between the first inorganic layer 103 and the polypropylene substrate layer 101 and the conductive layer 10 will be reduced.

[0122] Further, in order to improve the bonding strength between the first inorganic layer 103 and the polypropylene substrate layer 101, in some possible embodiments, please continue to refer to Figure 2 The preparation method further comprises a cleaning step before step S1, the cleaning step comprising:

[0123] S01, ultrasonically cleaning the polypropylene substrate layer 101 with distilled water, anhydrous ethanol, acetone, and anhydrous ethanol in sequence, and vacuum baking.

[0124] Before forming the first inorganic layer 103 on the side of the polypropylene substrate layer 101, the polypropylene substrate layer 101 is ultrasonically cleaned with distilled water, anhydrous ethanol, acetone, and anhydrous ethanol in sequence, and then vacuum-baked to remove residual chemical reagents and dirt on the surface of the polypropylene substrate layer 101 and improve the bonding strength between the first inorganic layer 103 and the polypropylene substrate layer 101.

[0125] In some possible embodiments, the polypropylene substrate layer 101 is ultrasonically cleaned using distilled water, anhydrous ethanol, acetone, and anhydrous ethanol in sequence, wherein the cleaning time of distilled water, anhydrous ethanol, acetone, and anhydrous ethanol is 1-10 minutes, the vacuum baking time is 1-20 minutes, and the vacuum baking temperature is 30-80°C.

[0126] Exemplarily, the time for ultrasonic cleaning of the polypropylene substrate layer 101 by using distilled water, anhydrous ethanol, acetone, and anhydrous ethanol is 5-8 minutes.

[0127] Exemplarily, the vacuum baking temperature is 40-50°C.

[0128] Exemplarily, the vacuum baking time is 8-10 minutes.

[0129] Furthermore, the method for ion cleaning the polypropylene substrate layer 101 includes:

[0130] S02. Perform ion cleaning on the polypropylene substrate layer 101. The power of ion cleaning is 0.01-5kW, the speed of ion cleaning is 0.1-20m / min, the process gas for ion cleaning is selected from at least one of oxygen, nitrogen, argon, hydrogen, and methane, and the gas volume of the process gas is 10-500sccm.

[0131] In step S02, after the polypropylene substrate layer 101 is ultrasonically cleaned, the polypropylene substrate layer 101 is placed in a vacuum chamber for ion cleaning, the power of the ion cleaning is 0.01-5kW, the speed of the ion cleaning is 0.1-20m / min, the process gas for ion cleaning is selected from at least one of oxygen, nitrogen, argon, hydrogen, and methane, and the gas volume of the process gas is 10-500sccm, which can further remove impurities on the surface of the polypropylene substrate layer 101.

[0132] In addition, the polypropylene substrate layer 101 is placed in a vacuum chamber for ion cleaning. The power of the ion cleaning is 0.01-5kW, and the speed of the ion cleaning is 0.1-20m / min. This can not only roughen the surface of the polypropylene substrate layer 101, but also activate the surface of the polypropylene substrate layer 101, so that dangling bonds are formed on the surface of the polypropylene substrate layer 101.

[0133] Polypropylene generally contains only carbon and hydrogen elements, and has few activated functional groups, and is generally difficult to directly form a bond with the first inorganic layer 103. The polypropylene substrate layer 101 is ion cleaned at a power of 0.01-5kW to form dangling bonds on the surface of the polypropylene substrate layer 101. The dangling bonds can form a bond with the first inorganic layer 103, thereby improving the bonding strength between the first inorganic layer 103 and the polypropylene substrate layer 101.

[0134] Ion cleaning of the polypropylene substrate layer 101 at a certain cleaning speed within a specific power range can ensure the cleaning effect, activate the surface of the polypropylene substrate layer 101, and reduce the impact of ion cleaning on the mechanical properties of the polypropylene substrate layer 101.

[0135] Exemplarily, the power of ion cleaning can be selected from one of 0.01 kW, 0.05 kW, 0.1 kW, 0.5 kW, 1 kW, 1.5 kW, 2 kW, 2.5 kW, 3 kW, 3.5 kW, 4 kW, 4.5 kW or 5 kW, or a range between any two thereof.

[0136] Usually, the polypropylene substrate layer 101 is rolled up and unrolled at a certain unwinding speed when preparing the composite current collector 100, so that the unrolled polypropylene substrate layer 101 passes through the corresponding section at a certain speed. The speed of ion cleaning refers to the speed at which the unrolled polypropylene substrate layer 101 passes through the ion cleaning section.

[0137] When the polypropylene substrate layer 101 is ion-cleaned at a power of 0.01-5 kW, the speed of the polypropylene substrate layer 101 is 0.1-20 m / min, which can reduce the probability of damage to the polypropylene substrate layer 101 during ion cleaning.

[0138] Exemplarily, the speed of ion cleaning can be selected from one of 0.1 m / min, 0.5 m / min, 1 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min, 10 m / min, 11 m / min, 12 m / min, 13 m / min, 14 m / min, 15 m / min, 16 m / min, 17 m / min, 18 m / min, 19 m / min or 20 m / min, or a range between any two of them.

[0139] In some possible embodiments, within the power range of 0.01-5 kW and the speed range of 0.1-20 m / min, when the power of ion cleaning increases, the speed of ion cleaning needs to be increased accordingly.

[0140] Exemplarily, when the power of ion cleaning is 0.1-1 kW, the speed of ion cleaning may be 1-5 m / min.

[0141] Exemplarily, when the power of ion cleaning is 1-5 kW, the speed of ion cleaning may be 10-20 m / min.

[0142] For example, the gas volume of the process gas for ion cleaning may be in the range of one or any two of 10 sccm, 50 sccm, 100 sccm, 150 sccm, 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm or 500 sccm.

[0143] In step S13, in some possible embodiments, the method of using an etching solution to etch the position of the polypropylene substrate layer 101 corresponding to the first through-hole structure 1041 to form the second blind hole structure 1042 includes:

[0144] An acid solution is applied to the side of the first inorganic layer 103 facing away from the polypropylene substrate layer 101 , so that the acid solution passes through the first through-hole structure 1041 to etch the polypropylene substrate layer 101 to form a second blind hole structure 1042 .

[0145] By etching the polypropylene substrate layer 101 at a position corresponding to the first through-hole structure 1041 with an acid solution, a second blind hole structure 1042 having a shape, size and distribution position similar to those of the first through-hole structure 1041 can be formed.

[0146] Furthermore, in order to reduce the effect of the acid solution on the first inorganic layer 103, in some possible embodiments, when etching the polypropylene substrate layer 101 to form the second blind hole structure 1042, an acid solution with a mass fraction of 10%-50% can be used, and etching can be performed at a coating temperature of 0-50°C for 1-60s.

[0147] Exemplarily, the mass fraction of the acid solution may be selected from one of 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, or a range between any two of them.

[0148] Exemplarily, the temperature for applying the acid solution may be selected from one of 0° C., 10° C., 20° C., 30° C., 40° C., or 50° C., or a range between any two of them.

[0149] Illustratively, the etching time may be selected from one of 1s, 5s, 10s, 15s, 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s or 60s, or a range between any two of them.

[0150] Using an acid solution with a mass fraction of 10%-50% and etching at a coating temperature of 0-50°C for 1-60s can reduce the degree of corrosion of the first inorganic layer 103 by the acid solution and reduce the influence of the acid solution on the shape, size and arrangement rule of the first through-hole structure 1041.

[0151] Further, in some possible embodiments, the acid solution can be selected from one or more of sulfuric acid, nitric acid, hydrobromic acid, chromic acid, selenic acid, perchloric acid, acetic acid, propionic acid, fatty acid, oleic acid, oxalic acid, maleic acid, hydroxypropionic acid, monochloroacetic acid or peracetic acid.

[0152] In some possible embodiments, in step S13, the position of the polypropylene substrate layer 101 corresponding to the first through hole structure 1041 is etched with an etching solution to form a second blind hole structure 1042, and the ratio of the depth of the second blind hole structure 1042 to the thickness of the polypropylene substrate layer 101 is 1:4.5-10.

[0153] Exemplarily, the ratio of the depth of the second blind hole structure 1042 to the thickness of the polypropylene substrate layer 101 can be 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10 or a range between any two of them.

[0154] The ratio of the depth of the second blind hole structure 1042 in the polypropylene substrate layer 101 to the thickness of the polypropylene substrate layer 101 is 1:4.5-10, which can reduce the influence of the excessive depth of the second blind hole structure 1042 on the mechanical properties of the polypropylene substrate layer 101, and reduce the influence of the excessive depth of the second blind hole structure 1042 on the bonding strength between the polypropylene substrate layer 101 and the conductive layer 10, and can further improve the structural stability of the composite current collector 100.

[0155] If the ratio of the depth of the second blind hole structure 1042 in the polypropylene substrate layer 101 to the thickness of the polypropylene substrate layer 101 is higher than 1:4.5, the depth of the second blind hole structure 1042 is too deep, which may easily lead to deterioration of the mechanical properties of the polypropylene substrate layer 101 and affect the mechanical properties of the composite current collector 100.

[0156] If the ratio of the depth of the second blind hole structure 1042 in the polypropylene substrate layer 101 to the thickness of the polypropylene substrate layer 101 is lower than 1:10, the depth of the second blind hole structure 1042 is too shallow, which may easily affect the adhesion between the polypropylene substrate layer 101 and the conductive layer 10 and affect the stability of the composite current collector 100.

[0157] Furthermore, in some possible embodiments, the depth of the second blind hole structure 1042 may be 1-1000 nm.

[0158] The depth of the second blind hole structure 1042 can be adjusted by adjusting the concentration of the etching solution, the etching temperature and the etching time.

[0159] Exemplarily, the depth of the second blind hole structure 1042 may be one of 1 nm, 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm, or a range between any two of them.

[0160] Furthermore, in some possible embodiments, the depth of the second blind hole structure 1042 is 40-100 nm.

[0161] Exemplarily, the thickness of the polypropylene substrate layer 101 is 4.5 μm, and the depth of the second blind hole structure 1042 is 40 nm.

[0162] Exemplarily, the thickness of the polypropylene substrate layer 101 is 4.5 μm, and the depth of the second blind hole structure 1042 is 50 nm.

[0163] Exemplarily, the thickness of the polypropylene substrate layer 101 is 4.5 μm, and the depth of the second blind hole structure 1042 is 100 nm.

[0164] For further information, please refer to Figure 2 , the preparation method provided in the embodiment of the present application comprises:

[0165] S2 . Fill the hole structure 104 with a conductive layer 10 , and the conductive layer 10 is located on the first inorganic layer 103 ; the surface layer of the conductive layer 10 is a metal layer 102 .

[0166] A conductive layer 10 is disposed on the first inorganic layer 103 and filled in the hole structure 104. The combination of the first inorganic layer 103 and the conductive layer 10 as well as the combination of the conductive layer 10 in the hole structure 104 with the first inorganic layer 103 and the polypropylene substrate layer 101 can be utilized to make the combination of the metal layer 102 in the conductive layer 10 and the polypropylene substrate layer 101 more firmly, thereby improving the structural stability of the composite current collector 100.

[0167] The conductive layer 10 includes a second inorganic layer 105 and a metal layer 102 located on the second inorganic layer 105. In step S2, the conductive layer 10 is filled in the hole structure 104, and the conductive layer 10 is located on the first inorganic layer 103, including:

[0168] S21 , forming a second inorganic layer 105 on a side of the first inorganic layer 103 facing away from the polypropylene substrate layer 101 , and at least a portion of the second inorganic layer 105 is filled in the hole structure 104 .

[0169] S22 , forming a metal layer 102 on a side of the second inorganic layer 105 facing away from the first inorganic layer 103 .

[0170] Among them, see Fig.10 and Figure 4 , Fig.10 FIG. 1 is a schematic diagram of a structure after forming the second inorganic layer 105 in step S21, and the composite current collector 100 after forming the metal layer 102 in step S22. Figure 4 .

[0171] The metal layer 102 in the conductive layer 10 is used for conducting electricity, and the second inorganic layer 105 in the conductive layer 10 may be conductive or insulating.

[0172] Furthermore, in some possible embodiments, the material of the second inorganic layer 105 may be selected from at least one of metals, alloys or oxides of copper, aluminum, chromium or nickel.

[0173] Exemplarily, the material of the second inorganic layer 105 can be selected from at least one of copper, aluminum, chromium, nickel, copper alloy, aluminum alloy, chromium alloy, nickel alloy, copper-aluminum alloy, chromium-nickel alloy, copper-aluminum-chromium-nickel alloy, copper oxide, aluminum oxide, chromium oxide or nickel oxide.

[0174] In some possible embodiments, the material of the second inorganic layer 105 may be the same as the material of the first inorganic layer 103. Exemplarily, the material of the second inorganic layer 105 and the material of the first inorganic layer 103 may both be selected from copper oxide.

[0175] In some possible embodiments, the material of the second inorganic layer 105 may be different from the material of the first inorganic layer 103. For example, the material of the first inorganic layer 103 may be selected from copper oxide, and the material of the second inorganic layer 105 may be selected from copper.

[0176] Furthermore, in step S21, the second inorganic layer 105 can be deposited or plated on the side of the first inorganic layer 103 away from the polypropylene substrate layer 101 and in the pore structure 104 by magnetron sputtering deposition, chemical vapor deposition, pulsed laser deposition or ion plating.

[0177] Exemplarily, the second inorganic layer 105 may be prepared by vacuum magnetron sputtering deposition.

[0178] In some possible embodiments, the thickness of the second inorganic layer may be 1-100 nm.

[0179] Illustratively, the thickness of the second inorganic layer 105 may be one of 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, or a range between any two thereof.

[0180] The thickness of the second inorganic layer 105 is 1-100 nm, which can improve the structural stability of the composite current collector 100. If the thickness of the second inorganic layer 105 is too low, it will affect the bonding strength between the second inorganic layer 105 and the first inorganic layer 103. If the thickness of the second inorganic layer 105 is too thick, it will affect the bonding strength between the metal layer 102 and the polypropylene substrate layer 101.

[0181] In step S22 , the metal layer 102 may be deposited or plated on the side of the second inorganic layer 105 away from the first inorganic layer 103 by magnetron sputtering deposition, chemical vapor deposition, pulsed laser deposition or ion plating.

[0182] Further, the material of the metal layer 102 can be selected from at least one of copper, aluminum, chromium or nickel. For example, the material of the metal layer can be selected from copper. For example, the material of the metal layer 102 can be selected from aluminum.

[0183] Further, in some possible embodiments, the material of the metal layer 102 may be the same as that of the second inorganic layer 105. When the material of the metal layer 102 is the same as that of the second inorganic layer 105, step S21 and step S22 may form the conductive layer 10 using the same deposition or plating process in the same coating device.

[0184] Furthermore, in some possible embodiments, the material of the metal layer 102 may be different from the material of the second inorganic layer 105. For example, the material of the second inorganic layer 105 may be selected from copper oxide, and the material of the metal layer 102 may be selected from copper.

[0185] Furthermore, the thickness of the metal layer 102 may be 50-200 nm.

[0186] Exemplarily, the thickness of the metal layer 102 can be selected from one of 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm or 200nm, or a range between any two thereof.

[0187] Furthermore, in some possible embodiments, the preparation method further includes an ion etching step between step S1 and step S22:

[0188] S23, performing ion etching on the side of the second inorganic layer 105 facing away from the first inorganic layer 103, the parameters of the ion etching include: bias voltage of -600 to -700 V, current of 0.4-0.5 A, temperature of 40-50° C., etching time of 15-20 min, and etching process gas selected from at least one of oxygen, nitrogen, argon, hydrogen or methane.

[0189] Ion etching the second inorganic layer 105 can form a velvet surface on the surface of the second inorganic layer 105 , and surface activation of the second inorganic layer 105 can form more dangling bonds, thereby improving the bonding strength between the second inorganic layer 105 and the metal layer 102 .

[0190] Furthermore, the present application example also provides a composite current collector 100 prepared according to the above method.

[0191] Furthermore, the example of the present application also provides an electrode, including a composite current collector and an electrode active material layer formed on a metal layer 102 of the composite current collector 100 .

[0192] Exemplarily, the electrode is a positive electrode, and the material of the electrode active material layer is selected from positive electrode active materials. Exemplarily, the positive electrode active material can be selected from lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate or nickel cobalt manganese ternary positive electrode material.

[0193] Exemplarily, the electrode is a negative electrode, and the material of the electrode active material layer is selected from negative electrode active materials. Exemplarily, the negative electrode active material can be selected from one or more of silicon-based negative electrode materials and graphite negative electrode materials.

[0194] Furthermore, the present application example also provides a battery, including the electrode provided in the present application example.

[0195] Exemplarily, the battery further includes a separator disposed between the positive electrode and the negative electrode.

[0196] Exemplarily, the battery further includes an electrolyte, which may be an electrolyte solution or a solid electrolyte.

[0197] The composite current collector of the present application is further described in detail below in conjunction with the embodiments.

[0198] Example 1

[0199] Embodiment 1 provides a composite current collector 100, and the preparation method is as follows:

[0200] (1) Ultrasonic cleaning step: A 4.5 μm thick high-strength heat-resistant random copolymer polypropylene substrate layer 101 is selected and the polypropylene substrate layer 101 is cleaned in the following steps: washing with distilled water for 5 min, ultrasonic cleaning with anhydrous ethanol for 8 min, ultrasonic cleaning with acetone for 8 min, ultrasonic cleaning with anhydrous ethanol for 8 min, and vacuum baking for 10 min at a baking temperature of 50°C.

[0201] (2) Ion cleaning step: The polypropylene substrate layer 101 cleaned in step (1) is placed in a vacuum magnetron sputtering coating device, and the chamber of the device is evacuated to a background vacuum of less than 5×10 -3 Pa, the temperature is 25° C. The oxygen gas volume for ion cleaning is 100 sccm, the ion cleaning power is 0.2 kW, and the cleaning speed is 1 m / min.

[0202] (3) Preparation of the first inorganic layer 103: The temperature in the equipment chamber was maintained constant, and oxygen was introduced to maintain the gas pressure at 0.18 Pa. Copper oxide was plated on the upper and lower surfaces of the polypropylene substrate layer 101 by vacuum magnetron sputtering to form the first inorganic layer 103. The deposition current was 10 A and the deposition time was 3 min. The thickness of the first inorganic layer 103 on both sides of the polypropylene substrate layer 101 was 10 nm.

[0203] (4) Laser etching: Take out the intermediate structure obtained in step (3), see Figure 4The first inorganic layer 103 is etched by laser etching to form a strip-shaped first through-hole structure 1041 . The width of the first through-hole structure 1041 is 150 nm, the depth is 10 nm, and the spacing between two adjacent first through-hole structures 1041 is 150 nm. The first inorganic layer is used as a chemical etching mask for the polypropylene substrate layer 101 .

[0204] (5) Chemical etching: At an ambient temperature of 40° C., the first inorganic layer 103 is coated with perchloric acid, and the position of the polypropylene substrate layer 101 corresponding to the first through-hole structure 1041 is chemically etched to form a second blind hole structure 1042 with a depth of 100 nm and a width of 150 nm on the upper and lower surfaces of the polypropylene substrate layer 101 corresponding to the first through-hole structure 1041. Chemical etching parameters: perchloric acid concentration 20%, etching time 10 s.

[0205] (6) Preparation of the second inorganic layer 105: The intermediate structure after chemical etching in step (5) is placed in a vacuum chamber, and the chamber is evacuated to a vacuum degree of less than 5×10 -3 Pa, the temperature is reduced to 25° C. A vacuum magnetron sputtering coating method is used to coat the first inorganic layer 103 and the hole structure 104 on both sides with a copper oxide coating as the second inorganic layer 105, with a deposition current of 10A and a deposition time of 3 minutes. The thickness of the second inorganic layer 105 on both sides is 10 nm.

[0206] (7) Ion etching: The temperature in the chamber of the equipment was maintained constant, and argon gas was introduced to maintain the gas pressure at 0.07 Pa. A bias voltage of 600 V was applied to the sample holder for ion etching, the cleaning current was 0.5 A, and the cleaning time was 10 min.

[0207] (8) Preparation of metal layer 102: The temperature in the chamber of the equipment was maintained constant, and argon gas was introduced to maintain the gas pressure at 0.18 Pa. A vacuum magnetron sputtering coating method was used to plate a copper coating on the second inorganic layer 105 on the upper and lower sides as the metal layer 102. The deposition current was 10 A, the deposition time was 120 min, and the thickness of the metal layer 102 on the upper and lower sides was 1000 nm.

[0208] The sample is taken out from the device to obtain a composite current collector 100 made of a polypropylene substrate with high bonding strength between the polypropylene substrate layer 101 and the metal layer 102 .

[0209] Example 2

[0210] Embodiment 2 provides a composite current collector 100, which is different from Embodiment 1 in that:

[0211] In step (4), the first through-hole structure 1041 formed by laser etching has a width of 50 nm and a depth of 10 nm, and the spacing between two adjacent first through-hole structures 1041 is 50 nm.

[0212] In step (5), the width of the second blind hole structure 1042 formed by chemical etching is 50 nm, the depth is 40 nm, and the spacing between two adjacent first through hole structures 1041 is 50 nm.

[0213] Example 3

[0214] Embodiment 3 provides a composite current collector 100, which is different from Embodiment 1 in that:

[0215] In step (2), ion cleaning step: the polypropylene substrate layer 101 cleaned in step (1) is placed in a vacuum magnetron sputtering coating device, and the chamber of the device is evacuated to a background vacuum of less than 5×10 -3 Pa, the temperature is 25° C. The oxygen gas volume for ion cleaning is 600 sccm, the ion cleaning power is 6 kW, and the cleaning speed is 20 m / min.

[0216] Example 4

[0217] Embodiment 4 provides a composite current collector 100, which is different from Embodiment 1 in that:

[0218] The ion etching in step (7) is replaced by laser etching: the intermediate structure in step (6) is taken out, and a groove is etched on the surface of the second inorganic layer 105 by laser etching, with a groove width of 50 nm and a depth of 2 nm.

[0219] Comparative Example 1

[0220] Comparative Example 1 provides a composite current collector, and the preparation method is as follows:

[0221] Step (1), step (2), step (3), step (4), step (5), step (6) and step (7) are not performed.

[0222] In step (8), a 4.5 μm thick high-strength heat-resistant random copolymer polypropylene substrate layer 101 is selected and placed in a vacuum magnetron sputtering coating device, and the chamber of the device is evacuated to a background vacuum of less than 5×10 -3 Pa, the temperature was raised to 50°C, and argon was introduced to maintain the gas pressure at 0.18 Pa; a copper coating was plated on the upper and lower surfaces of the high-strength heat-resistant random copolymer polypropylene substrate layer 101 by vacuum magnetron sputtering coating method to form a metal layer 102. The deposition current was 10A, the deposition time was 130 minutes, and the thickness of the upper and lower metal layers 102 was 1100 nm.

[0223] Comparative Example 2

[0224] Comparative Example 2 provides a composite current collector, which differs from Example 1 in that:

[0225] Step (2), step (3), step (4), step (6) and step (7) are not performed.

[0226] In step (5), at an ambient temperature of 40° C., perchloric acid is directly applied to the polypropylene substrate layer 101 after ultrasonic cleaning in step (1) for chemical etching. The concentration of perchloric acid and etching time are the same as those in Example 1.

[0227] In step (8), the polypropylene substrate layer 101 after chemical etching in step (5) is placed in a vacuum magnetron sputtering coating device, and the chamber of the device is evacuated to a background vacuum of less than 5×10 -3 Pa, the temperature was raised to 50°C, and argon was introduced to maintain the gas pressure at 0.18 Pa; a metal copper coating was plated on the upper and lower surfaces of the high-strength heat-resistant random copolymer polypropylene substrate layer 101 by vacuum magnetron sputtering coating method to form a metal layer 102. The deposition current was 10A, the deposition time was 130 minutes, and the thickness of the metal layer 102 on both the upper and lower sides was 1100 nm.

[0228] Comparative Example 3

[0229] Comparative Example 3 provides a composite current collector, which differs from Example 1 in that:

[0230] Step (3), step (4), step (6) and step (7) are not performed.

[0231] In step (5), at an ambient temperature of 40° C., perchloric acid is directly applied to the polypropylene substrate layer 101 after ion cleaning in step (2) for chemical etching. The concentration of perchloric acid and etching time are the same as those in Example 1.

[0232] In step (8), the polypropylene substrate layer 101 after chemical etching in step (5) is placed in a vacuum magnetron sputtering coating device, and the chamber of the device is evacuated to a background vacuum of less than 5×10 -3 Pa, the temperature was raised to 50°C, and argon was introduced to maintain the gas pressure at 0.18 Pa; a metal copper coating was plated on the upper and lower surfaces of the high-strength heat-resistant random copolymer polypropylene substrate layer 101 by vacuum magnetron sputtering coating method to form a metal layer 102. The deposition current was 10A, the deposition time was 130 minutes, and the thickness of the metal layer 102 on both the upper and lower sides was 1000 nm.

[0233] Comparative Example 4

[0234] Comparative Example 4 provides a composite current collector, which differs from Example 1 in that:

[0235] The chemical etching of step (5) is not performed. Step (6) Preparation of the second inorganic layer 105: The intermediate structure after laser etching in step (4) is placed in a vacuum chamber, and the chamber of the equipment is evacuated to a vacuum degree of less than 5×10-3 Pa, the temperature is reduced to 25° C. A vacuum magnetron sputtering coating method is used to coat the first inorganic layer 103 on both sides and the first through-hole structure 1041 with a copper oxide coating as the second inorganic layer 105. The deposition current is 10A, the deposition time is 3 minutes, and the thickness of the second inorganic layer 105 on both sides is 10 nm.

[0236] Comparative Example 5

[0237] Comparative Example 5 provides a composite current collector, which differs from Example 1 in that:

[0238] The ion cleaning step of step (2) is not performed; in step (3), the first inorganic layer 103 is directly plated on the upper and lower surfaces of the polypropylene substrate layer 101 after ultrasonic cleaning in step (1).

[0239] Comparative Example 6

[0240] Comparative Example 6 provides a composite current collector, which differs from Example 1 in that:

[0241] Steps (4) and (5) are not performed. In step (6), the second inorganic layer 105 is prepared by placing the structure obtained in step (3) into a vacuum chamber, and evacuating the chamber of the equipment to a vacuum degree of less than 5×10 -3 Pa, the temperature is 25° C. A vacuum magnetron sputtering coating method is used to coat copper oxide coatings on the first inorganic layer 103 on both sides as the second inorganic layer 105, the deposition current is 10A, the deposition time is 3 minutes, and the thickness of the second inorganic layer 105 on the upper and lower sides is 10 nm.

[0242] Test Example 1

[0243] XPS test was performed on the polypropylene substrate layer 101 provided in step (1) of Example 1 and the polypropylene substrate layer 101 obtained after ion cleaning in step (2). The test results are as follows: Fig.11 and Fig.12 As shown, Fig.11 This is the XPS test image before ion cleaning. Fig.12 This is the XPS test image after ion cleaning.

[0244] Result analysis:

[0245] from Fig.11 and Fig.12 It can be seen that in Example 1 of the present application, the polypropylene substrate layer 101 is subjected to ion cleaning, which can activate the surface of the polypropylene substrate layer 101 and form dangling bonds such as CO and C=O. Fig.11 The presence of CO bonds is due to contamination of the surface of the PP base film.

[0246] Test Example 2

[0247] The composite current collectors 100 provided in Examples 1-4 and Comparative Examples 1-6 were subjected to a 180° peeling test to detect the bonding strength.

[0248] Testing instrument: universal testing machine.

[0249] Testing environment: room temperature 23°C, humidity 50%.

[0250] Test method: Stick 50mm×19mm (length×width) 3M tape on the upper end of the steel plate; stick the composite current collector 100 to be tested on the tape, and the composite current collector 100 should be parallel to the steel plate. Fix the lower end of the steel plate on the lower fixture, and clamp the diaphragm to be tested on the end without the tape in the upper fixture; start the test machine and conduct the test; after the sample is peeled off, read the maximum peeling force, and the test results are shown in Fig.13 .

[0251] like Fig.13 As shown, by comparing Examples 1-4 and Comparative Examples 1-6, it can be seen that the binding force of the composite current collector 100 provided by Examples 1-4 is higher than the binding force of the composite current collector 100 provided by Comparative Examples 1-6, indicating that the embodiment of the present application forms dangling bonds by ion cleaning the polypropylene substrate layer 101, and forms a regularly distributed second blind hole structure 1042 by chemically etching the polypropylene substrate layer 101, and then arranges a conductive layer 10 in the first inorganic layer 103 and the second blind hole structure 1042, which can enhance the bonding strength between the layers of the composite current collector 100 and improve the stability of the composite current collector 100.

[0252] Comparing Example 1, Comparative Example 5 and Comparative Example 6, Comparative Example 5 did not perform ion cleaning, and Comparative Example 6 did not form a regularly distributed pore structure 104. The binding force of the composite current collector 100 obtained in Comparative Example 5 and Comparative Example 6 was less than the binding force of the composite current collector 100 obtained by performing ion cleaning and forming a regularly distributed pore structure in Example 1. Moreover, the sum of the binding forces of Comparative Example 5 and Comparative Example 6 is still less than that of Example 1. In addition, comparing Example 1 and Example 3, the binding force of the composite current collector 100 provided in Example 1 is greater than that of Example 3, indicating that ion cleaning of the polypropylene substrate layer 101 at a power of 0.01-5kW to activate its surface can further enhance the stability of the composite current collector 100.

[0253] Combining Example 1 and Example 2, it can be seen that the second blind hole structure 1042 of the polypropylene substrate layer 101 of Example 1 has a depth of 100 nm and a width of 150 nm, and the second blind hole structure 1042 of the polypropylene substrate layer 101 of Example 2 has a depth of 40 nm and a width of 50 nm. It is measured that the binding force of Example 1 is greater than the binding force of Example 2, indicating that providing a second blind hole structure 1042 of a suitable size at the polypropylene substrate layer 101 can further improve the binding force of the composite current collector 100.

[0254] Test Example 3

[0255] The battery using the composite current collector 100 provided in Example 1, Example 3, Example 4, Comparative Example 2 and Comparative Example 4 was subjected to a 1C cycle charge-discharge cycle test. The test results are shown in FIG. Fig.14 shown.

[0256] from Fig.14 It can be seen that the battery using the composite current collector 100 provided in Example 1 has the highest cycle capacity retention rate, indicating that ion cleaning of the polypropylene substrate layer 101 at a power of 0.01-5 kW can further improve the cycle performance of the battery.

[0257] In Example 3, the power of ion cleaning exceeds 5kW, which will damage the polypropylene substrate layer 101, causing the battery discharge capacity to decay slowly, which will affect the battery cycle performance. Comparing Example 1 and Example 4, Example 1 uses ion etching for the second inorganic layer 105. Compared with the method of using laser etching to form grooves on the second inorganic layer 105 in Example 4, the battery cycle performance provided by Example 1 is higher than the battery cycle performance provided by Example 4, indicating that ion etching of the second inorganic layer 105 roughens the surface of the second inorganic layer 105 and forms hanging bonds on its surface. Therefore, the bonding strength between the Cu metal layer 102 and the second inorganic layer 105 in Example 1 is much greater than that in Example 5.

[0258] In Comparative Example 2, perchloric acid is directly used to chemically etch the polypropylene substrate layer 101, and a regularly distributed second blind hole structure 1042 cannot be formed, so that the bonding force of the plating layer of Comparative Example 2 is weaker than that of Example 1, Example 3 and Example 5. When the composite current collector provided in Comparative Example 2 is applied to a battery, the cycle performance of the battery will be reduced.

[0259] In Comparative Example 4, only ion etching roughening treatment was performed on the substrate, and chemical etching was not performed to form a regularly distributed second blind hole structure 1042, so that the bonding strength of the plating layer of Comparative Example 4 is weaker than that of Example 1, Example 3 and Example 5. When the composite current collector provided by Comparative Example 4 is applied to a battery, the cycle performance of the battery will be reduced.

[0260] The preparation method provided in the example of the present application is used to prepare a composite current collector, so that the bonding strength between the polypropylene substrate layer 101 and the metal layer 102 is high, the structural stability of the composite current collector 100 is good, the preparation cost is low, and it is suitable for large-scale production.

[0261] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a composite current collector, characterized in that: include: S1, performing ion cleaning on at least one side of the polypropylene substrate layer to form dangling bonds on the surface of the polypropylene substrate layer; A first inorganic layer is formed on the surface of the polypropylene substrate layer, and a plurality of pore structures penetrating the first inorganic layer are provided on the first inorganic layer, wherein the pore structures extend into the polypropylene substrate layer but do not penetrate the polypropylene substrate layer; and the pore structures are regularly distributed in the first inorganic layer; S2. Filling a conductive layer in the hole structure, and the conductive layer is located on the first inorganic layer; the conductive layer includes a second inorganic layer and a metal layer, the second inorganic layer is filled in the hole structure and is located on the first inorganic layer, and the metal layer is located on the second inorganic layer.

2. The preparation method according to claim 1, characterized in that: The step of performing ion cleaning on the polypropylene substrate layer to form dangling bonds on the surface of the polypropylene substrate layer comprises: The polypropylene substrate layer is subjected to ion cleaning, the power of the ion cleaning is 0.01-5kW, the speed of the ion cleaning is 0.1-20m / min, the process gas for the ion cleaning is selected from at least one of oxygen, nitrogen, argon, hydrogen, and methane, and the gas volume of the process gas is 10-500sccm.

3. The preparation method according to claim 1, characterized in that: The hole structure penetrates two opposite ends of the first inorganic layer in the width direction, and a plurality of the hole structures are evenly spaced; Alternatively, a plurality of the hole structures are arranged in an array in the first inorganic layer.

4. The preparation method according to claim 1, characterized in that: In step S1, the step of providing a plurality of hole structures penetrating the first inorganic layer on the first inorganic layer, wherein the hole structures extend into the polypropylene substrate layer but do not penetrate the polypropylene substrate layer, comprises: The first inorganic layer is laser etched to form a plurality of first through hole structures spaced apart to expose the polypropylene substrate layer; the polypropylene substrate layer is etched at positions corresponding to the first through hole structures using an etching solution to form second blind hole structures, and the first through hole structures and the second blind hole structures together form the hole structure.

5. The preparation method according to claim 4, characterized in that: The ratio of the depth of the second blind hole structure to the thickness of the polypropylene substrate layer is 1:4.5-10; Optionally, the depth of the second blind hole structure is 1-1000 nm.

6. The preparation method according to claim 5, characterized in that: Along the first direction, the ratio of the width of the hole structure to the spacing between two adjacent hole structures is 1:1-20; Optionally, the width of the pore structure is 1-500 nm, and the distance between two adjacent pore structures is 1-500 nm.

7. The preparation method according to claim 6, characterized in that: The depth of the second blind hole structure is 50-100 nm; And / or, the width of the pore structure is 150-200 nm, and the distance between two adjacent pore structures is 150-200 nm.

8. The preparation method according to claim 4, characterized in that: The step of etching the polypropylene substrate layer at a position corresponding to the first through-hole structure using an etching solution to form the second blind hole structure comprises: An acid solution is applied to a side of the first inorganic layer away from the polypropylene substrate layer, so that the acid solution passes through the first through-hole structure to etch the polypropylene substrate layer to form the second blind hole structure.

9. The preparation method according to claim 8, characterized in that: The materials of the first inorganic layer and the second inorganic layer are independently selected from at least one of the metals, alloys or oxides of copper, aluminum, chromium or nickel; the material of the metal layer is selected from at least one of copper, aluminum, chromium or nickel; Optionally, the mass fraction of the etching solution is an acid solution of 10%-50%, the application temperature is 0-50° C., and the etching time is 1-60 s; Optionally, the acid solution is selected from one or more of sulfuric acid, nitric acid, hydrobromic acid, chromic acid, selenic acid, perchloric acid, acetic acid, propionic acid, fatty acid, oleic acid, oxalic acid, maleic acid, hydroxypropionic acid, monochloroacetic acid or peracetic acid.

10. The preparation method according to claim 1, characterized in that: The preparation method further comprises a cleaning step before step S1, wherein the cleaning step comprises: S01. Ultrasonic cleaning of the polypropylene substrate layer is performed using distilled water, anhydrous ethanol, acetone, and anhydrous ethanol in sequence, and vacuum baking is performed.

11. The preparation method according to claim 1, characterized in that: In step S1 , the first inorganic layer is formed on two opposite surfaces of the polypropylene substrate layer.

12. The preparation method according to any one of claims 1 to 11, characterized in that: In step S2, the conductive layer is filled in the hole structure, and the conductive layer is located on the first inorganic layer, including: The second inorganic layer is formed on the side of the first inorganic layer away from the polypropylene substrate layer, and at least a part of the second inorganic layer is filled in the hole structure; the metal layer is formed on the side of the second inorganic layer away from the first inorganic layer.

13. The preparation method according to claim 12, characterized in that: The preparation method also includes: before forming the metal layer on the side of the second inorganic layer away from the first inorganic layer, ion etching the side of the second inorganic layer away from the first inorganic layer, the parameters of the ion etching include: bias voltage of -600 to -700 V, current of 0.4-0.5 A, temperature of 40-50° C., etching time of 15-20 min, and etching process gas selected from at least one of oxygen, nitrogen, argon, hydrogen or methane.

14. The preparation method according to claim 1, characterized in that: The preparation methods of the first inorganic layer, the second inorganic layer and the metal layer are independently selected from at least one of magnetron sputtering deposition, chemical vapor deposition, pulsed laser deposition or ion plating; Optionally, the thickness of the first inorganic layer and the second inorganic layer is 1-100 nm; Optionally, the thickness of the metal layer is 50-200 nm.

15. A composite current collector prepared according to the preparation method according to any one of claims 1 to 14.

16. A battery, characterized in that: Comprising the composite current collector according to claim 15.

Citation Information

Cited By

  • Composite current collector and preparation method thereof, electrode plate and secondary battery

    CN121065651A

  • Composite current collector and its preparation method, electrode sheet, secondary battery

    CN121065651B